Fish processing waste: a novel source of non‐conventional functional proteins. (1st October 2022) - Rana, Sudha; Singh, Arashdeep; Surasani, Vijay Kumar Reddy; Kapoor, Swati; Desai, Ajay; Kumar, Siddhnath
Summary: Fish waste has now become one of the serious problems worldwide, and its disposal without proper management could result in serious environmental pollution and nutrient loss. These wastes contain several biological and nutritional compounds, if recovered has a lot of promise. With the recent technological developments, many bioactive and functional compounds can be recovered from these wastes. The vast quantity of bioactive chemicals found in seafood processing by‐products has prompted the development of valorisation strategies for their extraction. The future of fish processing waste for reuse and bioconversion is bright with the right mindset and achieve progress in the future. Proteins have advanced significantly in recent years, piquing the interest of many academics around the world. Therefore, fish proteins can be extracted from the fish waste and can be further utilised for human and animal purposes in form of protein isolate, hydrolysate, gelatin, collagen, silage and fish meal. Abstract : Functional proteins from fish processing waste.